Giełdy towarowe a nowe wymagania organizacyjno-prawne - Birski, Adam (Commodity Exchange and New Organizational-Legal Requirements, 2006)
The paper presents changes in commodity exchange development, taking new organizational-legal requirements into special consideration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 83-90